2015
DOI: 10.1371/journal.pone.0120950
|View full text |Cite
|
Sign up to set email alerts
|

1H-NMR and MS Based Metabolomics Study of the Intervention Effect of Curcumin on Hyperlipidemia Mice Induced by High-Fat Diet

Abstract: Curcumin, a principle bioactive component of Curcuma longa L, is well known for its anti-hyperlipidemia effect. However, no holistic metabolic information of curcumin on hyperlipidemia models has been revealed, which may provide us an insight into the underlying mechanism. In the present work, NMR and MS based metabolomics was conducted to investigate the intervention effect of curcumin on hyperlipidemia mice induced by high-fat diet (HFD) feeding for 12 weeks. The HFD induced animals were orally administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 50 publications
5
40
0
Order By: Relevance
“…Also, the results of this study showed that there was a correlation between the expression level of miRNA-146a and study parameters such as EC 50 , maximum response, IL-1β, IRAK1, TRAF6, NF-kB, triglyceride, and HDL. In DIO groups, serum levels of TG, TC, LDL, and HDL were remarkably increased compared with those in the normal diet groups, indicating the occurrence of hyperlipidemia, which was similar to previous studies [45,46]. Given that it has been shown that free fatty acids can activate inflammatory pathways in tissues [7], the authors do not rule out the effect of lipid profiles in alteration of cellular pathways.…”
Section: Figsupporting
confidence: 82%
“…Also, the results of this study showed that there was a correlation between the expression level of miRNA-146a and study parameters such as EC 50 , maximum response, IL-1β, IRAK1, TRAF6, NF-kB, triglyceride, and HDL. In DIO groups, serum levels of TG, TC, LDL, and HDL were remarkably increased compared with those in the normal diet groups, indicating the occurrence of hyperlipidemia, which was similar to previous studies [45,46]. Given that it has been shown that free fatty acids can activate inflammatory pathways in tissues [7], the authors do not rule out the effect of lipid profiles in alteration of cellular pathways.…”
Section: Figsupporting
confidence: 82%
“…Another NMR-and MS-based study investigated the intervention effect of curcumin on hyperlipidemic mice induced by a high-fat diet. 88 While the serum biochemical assay indicated that treatment of curcumin improves the lipid profiles, metabolic pathways derived from urine metabolic profiles provided more detail and indicated reversal of the metabolic disorder.…”
Section: Combining Nmr and Msmentioning
confidence: 99%
“…3-5 respectively. The identification of splitting and chemical shift of metabolites was accomplished by reference to the relevant literature (Fan 1996;Bollard et al 2000;Li et al 2015), and the resulting identification of metabolites is shown in S3 Table (a, b, c). The metabolomics results are presented using the OPLS-DA model (Fig.…”
Section: Metabolomics Analysis Based On 1 H-nmrmentioning
confidence: 99%